Improving Reading Skills At First Class Students Sdn 04 Koto Ranah Kecamatan Iv Nagari Bayang Utara Kabupaten Pesisir Selatan Through Model Of Singing Learning - Jaminar Jaminar (Fakultas Sastra Universitas Ekasakti, 2018)
The existence of elementary school as a basic educational institution is very high to participate in helping children grow. For Students class I SDN 04 Koto Ranah District IV Nagari Bayang Utara Pesisir Selatan District Lesson Year 2015/2016 is a place to play, socialize and also learn is quite representative. In general, people know that learning in class I Sdn 04 Koto Ranah District IV Nagari Bayang Utara Pesisir Selatan District Lesson Year 2015/2016 apply the principle of playing while learning or learning while playing. But in its application, it turns out that between theory and practice are not aligned. It was found that in the first grade students of SDN 04 Koto Ranah, Sub District IV Nagari Bayang Utara, Pesisir Selatan District, the Lesson Year 2015/2016 has been taught the lesson and its delivery as it is to teach the lessons to the children of Advanced School. Concerns arise when society generally thinks that the standard of teaching success in class I SDN 04 Koto Ranah Subdistrict IV Nagari Bayang Utara Pesisir Selatan District Lesson Year 2015/2016 is students who have completed education in elementary school able to write, read and count. Parents will feel proud when their son graduated from elementary school has been fluent in reading, writing and counting. Based on what the authors have done, can be drawn some conclusions that: Reading practice in teaching and learning process with singing techniques more easily ditangkapa by grade I SDN 04 Koto Ranah District IV Nagari Bayang Utara Pesisir Selatan District Lesson 2015/2016. During this activity, there is a seriousness of the children to follow the lesson. Children can learn to read without feeling depressed and always in a pleasant atmosphere. The results of monitoring quantitatively shows that 75% of children are able to read smoothly so that invites students class I SDN 04 Koto Ranah District IV Nagari Bayang North Pesisir Selatan District Lessons 2015/2016 reading practice with singing techniques proved to foster interest in reading children early on. A teacher meeting program with parents who are held once a month before delivering materials to children is very influential in helping children to succeed in SDN 04 Koto Ranah Sub District IV Nagari Bayang Utara Pesisir Selatan District Lesson 2015/2016. The author realizes that the delivery of the material has not been implemented optimally, given the number of children who exceed the capacity. If implemented more intensively and with the ideal ratio of teachers and children, then the quantitative and qualitative of course the result will be better.